Dark matter in the Milky Way: uncertainties on its distribution and implications on its particle nature - Benito, Maria [UNESP] (Universidade Estadual Paulista (Unesp), 2019)
The detailed knowledge of the dark matter (DM) distribution in the Milky Way (MW) is important for understanding the interplay between baryons and DM in the processes involved in galaxy formation and evolution. It is further a key element for experiments that aim to directly or indirectly detect the DM particle due to theoretically predicted non-negligible, weak interactions between DM and Standard Model particles. In this thesis, we aim to determine the distribution of DM in our Galaxy. First, we constrain the density profile of the DM halo by means of kinematical tracers of the total gravitational potential. We use objects in circular orbits around the Galactic centre (GC) as tracers of the total dynamical mass. By subtracting from the observed rotation velocities the velocities predicted for the visible component of the Galaxy (stars plus gas) -under the assumption of Newtonian gravity- we derive constraints on the DM distribution in the MW once a given parameterisation for the DM density profile is adopted. For the distribution of the visible, baryonic component of the Galaxy, we adopt a large array of observationally inferred, three-dimensional density profiles. In this way, we bracket current uncertainties on the shape and the normalisation of the Galactic visible component. Our determination of the DM density profile in the MW proceeds from astrophysical observations. These observations have sizeable uncertainties that need to be properly taken into account. We further present a full data-driven analysis that quantifies astrophysical uncertainties that affect the determination of the DM distribution in the MW, and therefore, the interpretation of results from direct and indirect DM particle searches. Furthermore, we study the DM distribution in the inner 2 kpc of the Galaxy. The inner Galactic region is dynamically dominated by baryons, and it is at the centre of a long-standing debate on whether the DM profile in the inner regions of galaxies is core or cusp. In our analysis, we adopt an estimate of the total dynamical mass within the inner 2 kpc of the MW. By simply subtracting from the total mass the stellar mass within the region under study, we infer the corresponding DM mass. We further study how this allowed DM mass translates into the parameter space of a particular parameterisation for the DM density profile. Finally, we present a methodology based on kinematical tracers of the total gravitational potential of the Galaxy that can be used for testing modified gravity theories at the scale of spiral galaxies.

O conhecimento detalhado da distribuição da matéria escura na Via Láctea é importante para a compreensão da interação entre bariões e matéria escura nos processos envolvidos na formação e evolução das galáxias. Além disso, é um elemento-chave para experimentos que objetivam detectar direta ou indiretamente a partícula de matéria escura devido a interações fracas, desprezíveis e teoricamente previstas entre as partículas de matéria escura e Modelo Padrão. Nesta tese, pretendemos determinar a distribuição da matéria escura na nossa galáxia. Primeiro, restringimos o perfil de densidade do halo matéria escura por meio de traçadores cinemáticos do potencial gravitacional total. Usamos objetos em órbitas circulares ao redor do centro galáctico como traçadores da massa dinâmica total. Ao subtrair das velocidades de rotação observadas as velocidades previstas para o componente visível da galáxia (estrelas mais gás) - sob a hipótese da gravidade newtoniana - derivamos restrições na distribuição da matéria escura na nossa Galáxia, uma vez que uma dada parametrização para o perfil de densidade da matéria escura é adotado. Para a distribuição do componente visível e bariônico da Galáxia, adotamos uma grande variedade de perfis de densidade tridimensionais observados e inferidos. Desta forma, colocamos as incertezas atuais na forma e na normalização do componente visível Galáctico. Nossa determinação do perfil de densidade da matéria escura na Galáxia provém de observações astrofísicas. Essas observações têm incertezas consideráveis que precisam ser devidamente levadas em conta. Além disso, apresentamos uma análise que quantifica as incertezas astrofísicas que afetam a determinação da distribuição da matéria escura na Via Láctea e, portanto, a interpretação dos resultados das buscas diretas e indiretas de partículas da matéria escura. Além disso, estudamos a distribuição da matéria escura nos 2 kpc centrais da Galáxia. A região galáctica central é dinamicamente dominada por bariones, e está no centro de um debate de longa data sobre se o perfil da matéria escura nas regiões centrais das galáxias é núcleo ou cúspide. Em nossa análise, adotamos uma estimativa da massa dinâmica total dentro dos 2 kpc centrais da Via Láctea. Simplesmente subtraindo da massa total a massa estelar dentro da região em estudo, inferimos a massa correspondente da matéria escura. Finalmente, apresentamos uma metodologia baseada em traçados cinemáticos do potencial gravitacional total da Galáxia que pode ser usada para testar teorias de gravidade modificada na escala de galáxias espirais.
Matéria escura na Via Láctea: incertezas sobre sua distribuição e implicações em sua natureza de partículas
Keywords: Milky Way; Galaxy dynamics; Rotation curve; Dark matter